1990
DOI: 10.1016/0735-1097(90)90289-2
|View full text |Cite
|
Sign up to set email alerts
|

Preload dependence of fiber shortening rate in conscious dogs with left verntricular hypertrophy

Abstract: Employing the new concept of systolic myocardial stiffness, this study addresses the questions of linearity of the end-systolic stress-strain relations in left ventricular hypertrophy and the preload dependence of fiber shortening rate. Pressure overload hypertrophy was induced in six puppies by banding the ascending aorta. Ultrasonic crystals were implanted for measurement of short axis and wall thickness in the six dogs with hypertrophy and in five control dogs. A pressure catheter was inserted through the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Results comparable with the present study are theoretically obtainable when midwall measurements are normalized or referenced to calculated values at zeroluminal volume rather than end-diastolic dimensions, as have been used previously (12,13,20,27,30). The mathematical relationship between wall-thickness ratios and midwall-diameter ratios is not linear, however (see the APPENDIX); therefore, the shapes of the relationships with stress, work, and power may also be different.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Results comparable with the present study are theoretically obtainable when midwall measurements are normalized or referenced to calculated values at zeroluminal volume rather than end-diastolic dimensions, as have been used previously (12,13,20,27,30). The mathematical relationship between wall-thickness ratios and midwall-diameter ratios is not linear, however (see the APPENDIX); therefore, the shapes of the relationships with stress, work, and power may also be different.…”
Section: Discussionsupporting
confidence: 70%
“…Other noninvasive methods of ventricular performance assessment, such as FS (7), velocity of circumferential fiber shortening (VCF) (5), and corrected VCF (VCF c ) (8), use end diastole as a reference state. This is also true for some invasive methods (20). However, natural variation in end-diastolic distension from beat to beat would be expected to result in additional random scatter not accounted for by an underlying Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Supernormal LV performance has been recognized in subsets of humans 12,13 and animals with experimental hypertension, 14 due to an increased contractility and/or the use of preload reserve, especially in the absence of adequate LV hypertrophy. 15,16 As shown in human studies, 17,18 in rats with renovascular hypertension 19 and in Dahl salt-sensitive animals, 20 the assessment of LV function by measuring the extent of fiber shortening at the endocardium level is less appropriate than using the value calculated at the midwall. This region represents both the anatomical site of circumferential myocardial fibers and the approximate level where mean transmural wall stress is applied.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty years ago, in an experimental model of pressure-overload LV hypertrophy, Mirsky et al [ 26 ] demonstrated that the correction for preload, considerably lower in animals with versus without pressure overload-induced concentric LV hypertrophy for any given afterload, entirely eliminated an artifactual depression of LV contractility derived from end-systolic stress–shortening relations when preload was not accounted for. In brief, depressed LV systolic performance might result not from an apparent impairment of the intrinsic LV contractile state, but from a smaller LVd according to the Frank–Starling law.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, circumferential LV strain [ 30 , 31 , 32 , 33 ] and meridional ESS [ 34 ] were comparable in P-LFLG-AS and NFHG-AS, in contrast to early impairment of longitudinal LV systolic function in P-LFLG-AS [ 1 , 30 , 31 , 32 ] which was linked to elevated Zva and diminished systemic arterial compliance [ 30 , 31 , 32 , 34 ]. Importantly, mwFS is largely controlled by circumferentially oriented fibers which predominate in the myocardial midwall, while subendocardial fibers are mainly oriented in the meridional direction [ 14 , 15 , 16 , 17 , 26 ].…”
Section: Discussionmentioning
confidence: 99%